2016
DOI: 10.1039/c5an02274f
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating the inter pillar gap in pillar array ultra-thin layer planar chromatography platforms

Abstract: An advantage of separation platforms based on deterministic micro- and nano-fabrications, relative to traditional systems based on packed beds of particles, is the exquisite control of all morphological parameters. For example, with planar platforms based on lithographically-prepared pillar arrays, the size, shape, height, geometric arrangement, and inter pillar gaps can be independently adjusted. Since the inter pillar gap is expected to be important in determining resistance to mass transfer in the mobile ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Since the group of Regnier first used perfectly ordered pillars as the stationary-phase support structure in chromatography in 1998 [2], pillar array columns (PACs) have been studied intensively by a limited number of research groups [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. A dramatic reduction of the disorder related eddy dispersion or A-term of the van Deemter equation has been consistently demonstrated throughout the past decade, but also the freedom in external porosity, flow-through pore shape and channel depth turned out to be features that can be exploited to further tune and improve the column considerably.…”
Section: Introductionmentioning
confidence: 99%
“…Since the group of Regnier first used perfectly ordered pillars as the stationary-phase support structure in chromatography in 1998 [2], pillar array columns (PACs) have been studied intensively by a limited number of research groups [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. A dramatic reduction of the disorder related eddy dispersion or A-term of the van Deemter equation has been consistently demonstrated throughout the past decade, but also the freedom in external porosity, flow-through pore shape and channel depth turned out to be features that can be exploited to further tune and improve the column considerably.…”
Section: Introductionmentioning
confidence: 99%
“…The existence of an optimum in linear flow velocity, υ , is seen in the equation. In a prior work using similar PL pillar arrays, optimum flow rates range between approximately 0.1 and 0.7 cm/s . The optimum υ for the nanoscale DW arrays are greater (Supporting Information page 2).…”
Section: Resultsmentioning
confidence: 99%
“…The resulting pillars also had a mean diameter of 2 μm and a mean pillar gap of 1.5 μm. Although the previous work by Crane et al 24 showed the advantage of decreasing pillar and pillar gap size, slightly greater gap sizes were chosen so that greater thicknesses of PSO could be deposited without closing the interpillar gap.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…It is well-established that increasing the surface area of a stationary phase increases the retention of analyte in the system by providing more sites for sorption while simultaneously maintaining a thin sorbent layer . Desmet and co-workers demonstrated that porous silicon can be used to increase surface area in pressurized and confined ordered systems, while Clark and Olesik used a mat of spun polyacrylonitrile to generate a porous layer and create an open UTLC platform. , Previous research from our group has shown that highly ordered micropillar arrays, coated with a thin layer of silicon oxide and functionalized with a hydrocarbon reversed stationary phase, can produce plate heights of less than 1 μm in closed pressure-driven systems and plate heights on average of 2 μm in open, capillary-action-driven array systems. ,, Studies have found that room-temperature plasma-enhanced chemical vapor deposition (PECVD) of silicon oxide creates a thin, conformal porous silicon oxide (PSO) layer. , Crane et al were able to use PSO to investigate closing the gap between pillars and its effect on solvent flow and efficiency . In this work we examine the effect of applying PSO to UTLC systems for the purposes of investigating its effect on analyte retention.…”
mentioning
confidence: 99%
See 1 more Smart Citation